Clinical significance of stromal ER and PR expression in periampullary adenocarcinoma - Gustav Andersson; Sebastian Lundgren; Margareta Heby; Björn Nodin; Jacob Elebro; Karin Jirström (Biomarker Research, 2019)
Abstract Background Tamoxifen treatment has previously been reported to confer life-prolonging effects in patients with advanced pancreatic cancer, and most evidently so in women. None of these trials did however include biomarkers, and the relevance of female hormone signaling in pancreatic or other periampullary adenocarcinoma remains largely unexplored. The aim of this study was to examine the extent and potential clinical significance of estrogen receptor-α (ER) and progesterone receptor (PR) expression in pancreatic and other periampullary cancers. Methods ER and PR expression was examined using immunohistochemistry on tissue microarrays with primary tumors from a retrospective consecutive cohort of 175 patients with resected periampullary adenocarcinoma, with long-term clinical follow-up. Non-parametric and Chi square tests were applied to examine the associations of stromal ER and PR expression with patient and tumor characteristics. Kaplan-Meier analysis and log rank test were applied to illustrate survival differences in relation to ER and PR expression. Cox regression proportional hazards models were applied to examine the associations between investigative factors and risk of death and recurrence, and to test for interactions between KRAS mutation status and hormone receptor expression in relation to survival. Results Expression of both ER and PR was more frequent in the tumor-associated stroma than in the epithelium. A significant prognostic interaction, independent of tumor morphology, was found between stromal PR expression and KRAS mutation status in relation to both overall and recurrence-free survival (pinteraction = 0.026 and pinteraction = 0.005), in particular in women (pinteraction = 0.002 and pinteraction = 0.005). Specifically, stromal PR expression was associated with a prolonged survival in patients with KRAS-mutated tumors, whereas the opposite was seen for KRAS wild-type tumors. The prognostic value of ER positivity was limited to the subgroup of women with tumors of pancreatic origin. Conclusions These results demonstrate that stromal PR rather than ER expression, together with KRAS mutation status, provides long-term prognostic information in patients with periampullary adenocarcinoma. Further study into the mechanistic basis for these observations may unveil important clues to the pathogenesis of these cancers and open up for the discovery of novel treatment options.